OVERSTAY TEACHER TRANSFERS IN PUBLIC SCHOOLS IN SRI LANKA: IMPACT ON SCHOOL MANAGEMENT AND PERFORMANCE - Wijayatunga, Ameesha Ramithanjalee (Proceedings of the International Conference on Education, 2018)
In many developing countries, there is no clear policy on teacher transfers in the public sector. The transfers tend to be ad-hoc and based on personal interests, political interferences and other indirect factors with no regard to improving quality of education. In Sri Lanka teachers in public schools are transferred after 10years of continuous service in a given school. Studies in different countries show, involuntary transfers can cause stress in teachers leading to possible poor teaching performance of the transferees. However, it is admitted that transfers also help to increase the efficiency of teachers. The study presented in the paper examined how involuntary transfers impact on performance of teachers and management in public schools. The study is based on a survey conducted through a questionnaire and direct interviews in five selected schools in Colombo district representing urban and suburban areas. A random sample of teachers and the Principals of all five schools took part in the research. The study concludes that the teachers are generally not affected in personal life due to overstay transfers. The only visible impact due to housing issues can be mitigated with appropriate measures. Also overstay transfers do not have an adverse impact on the management and performance in the new school. Overall, staggered, selective and well-coordinated overstay transfers are beneficial to schools and can be used as an opportunity to implement measures to improve academic performance and management.